Bimaxillary orthognathic surgery for correction of dentoskeletal deformity: Case report - Pinto, Vitória Núbia Dias; Martins, Olga Beatriz Lopes; Becheleni, Marco Túllio; Neri , Anna Marina Teixeira Rodrigues; Barros, Mariana Oliveira; Silva, Thiago Fonseca; Falci, Saulo Gabriel Moreira (Seven Editora, 2023)
Class III dentoskeletal malocclusion is one of the most requested in terms of treatment. Request multidisciplinary therapy and a combination of orthodontics and surgery. Virtual pre-surgical planning helps minimize damage and achieve better results. The objective of this work is to describe the clinical picture of a patient with dentoskeletal deformity treated through bimaxillary orthognathic surgery, results obtained and postoperative follow-up. Orthognathic surgery has proven to be an effective treatment alternative to reestablish the function of the stomatognathic apparatus and balance facial aesthetics, combined with postoperative occlusal stability and patient satisfaction with the result. DOI:https://doi.org/10.56238/innovhealthknow-030